The Architecture of Magic. Toward a Canon of Scandinavian svartebøker? - Taglianetti, Luca (Folia Scandinavica Posnaniensia, 2025)
In the historical and cultural study of the impact of magical practices on everyday life in the Nordic region, a significant role is played by the examination of the composition, distribution, and use of black magic books commonly known as svartebøker. The widespread practice of composing, using, and transmitting these books is well-documented throughout the North as early as the 15th century. These are composite manuscripts that blend Latin formulas, invocations to saints and demons, remedies for improving one’s fortune or the health of livestock, spells to harm someone. However, comparisons across various manuscripts suggest that svartebøker generally followed a predetermined pattern based on local legends and beliefs, incorporating motifs of European scope. This pattern is reflected in the textual architecture of svartebøker across the Scandinavian region, likely creating a veritable canon of magical book composition. By analyzing some manuscripts from the Scandinavian area, this article seeks to highlight indispensable recurring patterns, widely diffused and reiterated over time, points that not only legitimize the remedies and formulas contained in the books but that also canonize a magical narrative structure. In addition, through folklore research, an attempt will be made to trace the origins of these patterns.